Chicago River bridges - McBriarty, Patrick T. (University of Illinois Press, 2013)
McBriarty presents the untold history and development of Chicago's iconic bridges, from the first wood footbridge built by a tavern owner in 1832 to the fantastic marvels of steel, concrete, and machinery of today. It is the story of Chicago as seen through its bridges, for it has been the bridges that proved critical in connecting and reconnecting the people, industry, and neighborhoods of a city that is constantly remaking itself.